A Remark on Vetrivel’s Existence Theorem on Ky Fan’s Best Approximant - Nashine, Hemant Kumar (Sarajevo Journal of Mathematics, 2024)
Vetrivel (1996) proved an existence theorem on Ky fan's best approximant for multifunction with open inverse values. The object of this paper is to present an improved and extended version of this result. 2000 Mathematics Subject Classification. 41A50, 47H10, 54H25